융합기술 연구 활성화를 위한 새로운 운영시스템 구축 - 김정호; 노형민 (한국경영공학회, 2012)
The purpose of this study was to develop a new management system for research institutions in the field of convergence technology in order to advance the field. For this study, investigations and analyses of properties, structures, and operational methods of existing convergence technology research institutions were conducted and a management system planning committee was formed to investigate the present status of research operations and development methods for convergence technology research in Korea. Also, case studies of successful management systems of research institutions in the field of convergence technology in Korea and abroad were carried out. A top-down approach was used for the analysis of convergence research and a bottom-up approach was used for a more detailed analysis. In this study, suggestions for ways to utilize alternative financial resources such as government funds are proposed. The study also suggests that a research team for convergence research should be formed under the prerequisite that it be temporary and flexible. It also emphasizes the importance of the leader, and concludes that it would be most appropriate to focus on research teams that are promoting large-scale convergence projects for its team composition and to support existing research teams that are capable of handling large-scale convergence research projects. A research management system involving a two-tier system composed of research leaders and coordinators and an open innovation research system that encourages active intellectual and personal exchanges with external agencies is proposed as a management model. In addition, the study proposes the following: an installation of a steering committee, a research infrastructure relating to spatial formation for communication, diversification of assessment methods, a systematic assessment and an evaluation system authorizing the research leaders to participate in the evaluation, and an improved incentive compensation system reflecting the evaluation results. The management system proposed in this study has been effectively applied to research institutions in the field of convergence technology in order to contribute to the advancement of convergence technology